Emerging Trends in Global Education a Qualitative Analysis of Thailand’s Ascendance as a Preferred Destination for Management Studies - Li, Ming; Supho, Ananya; Hirinburana, Vatita; Bunjitpimol, Pimkhwan; Keyanon, Sutharinee (Rajapark Journal, 2024)
This research aims to uncover the motivations of Chinese students opting for management studies in Thailand and to proffer strategic insights for augmenting the internationalization of higher education management in Thailand and elevating the caliber of study abroad services provided to international students. The research employed a questionnaire survey method targeting Chinese students studying management in Thailand, including 27 doctoral students, 70 undergraduates, and 32 master students, collecting over 122 valid responses. The study analyzed these responses using thematic analysis and grounded theory to identify relevant themes and keywords, construct a coding system, and develop a theoretical model of Chinese students’ choice of Thailand as a destination for management studies. Additionally, the study built a knowledge map to elucidate this motivation. The findings were found as follows: 1. geographical and economic considerations, educational system advantages, cultural and social engagement, personal and professional development, misinformation, and exploration and curiosity–these factors contribute to Chinese students’ decisions to study management in Thailand; 2. factors among practical considerations, the pursuit of personal, and professional enrichment, indicate a complex interaction.